1. ENDING THE CRIMINALIZATION OF MENTAL ILLNESS. (9th April 2019) - Leifman, Steven
Abstract: It is estimated that more than two million arrests in the United States each year involve people with Serious Mental Illnesses (SMI) – half of which are homeless at the time of their arrest. As a result, untrained and unprepared stakeholders in the criminal justice system have been forced to navigate an increasingly scarce system of care for people with mental illnesses. Jails have become places where a disproportionate number of people with SMI spend significant amounts of time; their ties to the community severed, their treatment needs unmet, and their illnesses made worse. Judge Leifman will discuss his journey into the mental health system, the legal and medical history that led to America's mental health crisis and the essential elements necessary to create an effective system of care that ultimately will transform the mental health and criminal justice systems and make jail the last option for people with serious mental illnesses, not the first.